Beneficial ex vivo immunomodulatory and clinical effects of clarithromycin in COVID-19. Issue 7 (July 2022) - Snow, Timothy Arthur Chandos; Longobardo, Alessia; Brealey, David; Down, Jim; Satta, Giovanni; Singer, Mervyn; Arulkumaran, Nishkantha
Abstract: Introduction: Macrolide antibiotics have immunomodulatory properties which may be beneficial in viral infections. However, the precise effects of macrolides on T cell responses to COVID, differences between different macrolides, and synergistic effects with other antibiotics have not been explored. Methods: We investigated the effect of antibiotics (amoxicillin, azithromycin, clarithromycin, and combined amoxicillin with clarithromycin) on lymphocyte intracellular cytokine levels and monocyte phagocytosis in healthy volunteer PBMCs stimulated ex vivo with SARS-CoV-2 S1+2 spike protein. A retrospective cohort study was performed on intensive care COVID-19 patients. Results: Co-incubation of clarithromycin with spike protein-stimulated healthy volunteer PBMCs ex vivo resulted in an increase in CD8 + (p = 0.004) and CD4 + (p = 0.007) IL-2, with a decrease in CD8 + (p = 0.032) and CD4 + (p = 0.007) IL-10. The addition of amoxicillin to clarithromycin resulted in an increase in CD8 + IL-6 (p = 0.010), decrease in CD8 + (p = 0.014) and CD4 + (p = 0.022) TNF-alpha, and decrease in CD8 + IFN-alpha (p = 0.038). Amoxicillin alone had no effect on CD4 + or CD8 + cytokines. Co-incubation of azithromycin resulted in increased CD8 + (p = 0.007) and CD4 + (p = 0.011) IL-2. There were no effects on monocyte phagocytosis. 102 COVID-19 ICU patients received antibiotics on hospital admission; 62 (61%) received clarithromycin. Clarithromycin use was associated with reduction in mortality on univariate analysis (p = 0.023), but not following adjustment for confounders (HR = 0.540; p = 0.076). Conclusions: Clarithromycin has immunomodulatory properties over and above azithromycin. Amoxicillin in addition to clarithromycin is associated with synergistic ex vivo immunomodulatory properties. The potential benefit of clarithromycin in critically ill patients with COVID-19 and other viral pneumonitis merits further exploration.